2022
DOI: 10.1002/adma.202207321
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmions Under Control—FIB Irradiation as a Versatile Tool for Skyrmion Circuits

Abstract: Magnetic data storage and processing offer certain advances over conventional technologies, amongst which nonvolatility and low power operation are the most outstanding ones. Skyrmions are a promising candidate as a magnetic data carrier. However, the sputtering of skyrmion films and the control of the skyrmion nucleation, motion, and annihilation remains challenging. This work demonstrates that using optimized focused ion beam irradiation and annealing protocols enables the skyrmion phase in W/CoFeB/MgO thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The deterministic skyrmion generation with an electrical operation is essential for the realistic design of SkRMs. To date, a few electrical approaches have been employed to drive skyrmion nucleation. ,, Table summarizes their main characteristics, together with the approach proposed here. A major issue for most of approaches is the temperature gradient resulting from Joule heating (such as nonuniform current-induced SOT, heating tip assisted) which can drive complex skyrmion dynamics. , For the irradiated pinning center-assisted technique, the skyrmion generation is a multistep process involving first a domain formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deterministic skyrmion generation with an electrical operation is essential for the realistic design of SkRMs. To date, a few electrical approaches have been employed to drive skyrmion nucleation. ,, Table summarizes their main characteristics, together with the approach proposed here. A major issue for most of approaches is the temperature gradient resulting from Joule heating (such as nonuniform current-induced SOT, heating tip assisted) which can drive complex skyrmion dynamics. , For the irradiated pinning center-assisted technique, the skyrmion generation is a multistep process involving first a domain formation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a few electrical approaches have been employed to drive skyrmion nucleation. ,, Table summarizes their main characteristics, together with the approach proposed here. A major issue for most of approaches is the temperature gradient resulting from Joule heating (such as nonuniform current-induced SOT, heating tip assisted) which can drive complex skyrmion dynamics. , For the irradiated pinning center-assisted technique, the skyrmion generation is a multistep process involving first a domain formation. Overall, previous methods rely on a more complicated generation process as compared to one proposed here based on the combination of a homogeneous current and a rectangular domain with reversed magnetization .…”
Section: Discussionmentioning
confidence: 99%
“…In order to create the artificial pinning sites, we exploit Ga + focused ion beam (FIB) irradiation. Studies on CoFeB/MgO already confirmed the possibility to tune the energy landscape, together with the magnetic parameters of the material, by irradiating the thin-film stack with He + ions , or with heavier ions such as Ga + . In a previous work on the Ta/CoFeB/MgO trilayer, it was shown that K eff can be increased up to a peak value by Ga + irradiation and then decreased for higher ion doses. Differently, lighter ions, such as He + , when traversing the material lead to other modifications of the magnetic properties, resulting in a monotonic reduction of the effective magnetic anisotropy as the ion dose increases .…”
Section: Introductionmentioning
confidence: 95%
“…Ultrathin magnetic films in direct contact with 4d or 5d heavy metals become the host of a wide range of spin–orbit coupling related phenomena including perpendicular magnetic anisotropy (PMA), the interfacial Dzyaloshinskii–Moriya interaction (i-DMI), chiral magnetic damping, the spin Hall effect (SHE), and spin–orbit torque (SOT). , The implementation of high-performance and energy-efficient spintronic devices requires an improvement in interface quality and a significant enhancement of these effects . The current approaches to modification of the crystal structure of thin films include ion beam irradiation, influence of laser pulses, and thermal annealing. , Previous studies of exchange coupled Co/Cu/Co systems demonstrated the significant enhancement of coercive force, saturation field, and magnetoresistance after annealing at temperatures ranging from 200 to 250 °C. …”
Section: Introductionmentioning
confidence: 99%
“…1,2 The implementation of high-performance and energy-efficient spintronic devices requires an improvement in interface quality and a significant enhancement of these effects. 3 The current approaches to modification of the crystal structure of thin films include ion beam irradiation, 4 influence of laser pulses, 5 and thermal annealing. 6,7 Previous studies of exchange coupled Co/Cu/Co systems demonstrated the significant enhancement of coercive force, saturation field, and magnetoresistance after annealing at temperatures ranging from 200 to 250 °C.…”
Section: ■ Introductionmentioning
confidence: 99%